Microlensing Events in Five Years of Photometry from the Zwicky Transient Facility - Ruocheng Zhai; Antonio C. Rodriguez; Shude Mao; Casey Y. Lam; Eric C. Bellm; Josiah Purdum; Frank J. Masci; Avery Wold (The Astrophysical Journal)
Microlensing has a unique advantage for detecting dark objects in the Milky Way, such as free-floating planets, neutron stars, and stellar-mass black holes. Most microlensing surveys focus on the Galactic bulge, where higher stellar density leads to a higher event rate. However, microlensing events in the Galactic plane have closer lenses and longer timescales, which leads to a greater chance of measuring microlens parallax, providing an additional constraint on the mass of the lens. This work searches for microlensing events in Zwicky Transient Facility (ZTF) Data Release 17 from 2018 to 2023 in the Galactic plane region. We find 124 high-confidence microlensing events and 54 possible events, all available online (see footnote 11). Thus, with 2 yr of additional ZTF data in DR17, we have more than doubled the number of microlensing events (60) found in the previous 3 yr DR5 search. In the event selection, we use the efficient EventFinder algorithm to detect microlensing signals, which could be used for large data sets such as future ZTF data releases or data from the Rubin Observatory Legacy Survey of Space and Time. Using detection efficiencies of ZTF fields obtained from catalog-level simulations, we calculate the mean Einstein timescale to be 〈 t _E 〉 = 51.7 ± 3.3 days, smaller than previous results of the Galactic plane but within 1.5 σ . We also calculate optical depths and event rates, although some caution is needed due to the use of visual inspection when creating our final sample. Spectroscopy of three possible candidates confirms their microlensing nature.